Υπολογισμός αντίστασης κυματισμού σε πλοία γεωμετρίας συστηματικών σειρών 60 με χρήση της θεωρίας δυναμικού και μελέτη της επίδρασης της ύπαρξης βολβού και των γεωμετρικών χαρακτηριστικών αυτού στη μεταβολή της αντίστασης κυματισμού - Τζάφος, Παναγιώτης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Ναυτικής και Θαλάσσιας Υδροδυναμικής, 2017)
By solving the potential theory, numerical experiments were conducted for ship models without and with a bulbous bow. The program used which implemented the potential solver is panelw.f and is developed by Professor Mr. Georgios Tzabiras. The results are evaluated and a conclusion about the benefits of the use of the bulb is drawn. Also, more numerical experiments were conducted for bulbs with different geometrical properties.